Juridical Analysis of Consumer Protection in Indonesian E-Commerce Transactions - Pijoh, Feibe E.; Rahmad, Riadi Asra; Mambu, Joupy G.Z (UNISSULA, 2024)
E-commerce creates a new dynamic in trade, connecting consumers with businesses from various regions and countries. However, consumers often face risks such as fraud, lack of transparency in transactions, and concerns regarding personal data protection, especially amid rising privacy violations. Existing regulations often struggle to fully address the complexities of these issues. This study employs a qualitative method with a normative juridical approach. The data source used in this research is secondary data. The primary legal foundations of this study are Law No. 8 of 1999 on Consumer Protection and Law No. 19 of 2016, which amends Law No. 11 of 2008 on Information and Electronic Transactions. This research identifies consumer rights, business obligations, and legal responsibilities inherent in electronic transactions. Although these laws provide a clear legal framework, there is a weakness in extending protection to businesses based outside the country, leaving consumers vulnerable to fraud. This study recommends the development of more comprehensive policies to enhance consumer protection, including regulations capable of addressing the challenges of globalization in e-commerce.